Single‐Atom Materials: Small Structures Determine Macroproperties. Issue 2 (11th February 2021) - Yang, Jiarui; Li, Wenhao; Wang, Dingsheng; Li, Yadong
Abstract : Single-Atom Materials The single‐atom materials (SAMs) have been explored a lot in recent years, but there are still many barriers needed to overcome, which hold back the practical use of SAM. In article number 2000051 by Dingsheng Wang and co‐workers, the main barriers and opportunities are discussed, aiming to provide a guideline for the research on the next step and push the acknowledgement of SAMs to a higher level.